Politics, death, and the devil : self and power in Max Weber and Thomas Mann - Goldman, Harvey (Berkeley : University of California Press, 1992)
This sequel to Harvey Goldman's well-received Max Weber and Thomas Mann continues his rich exploration of the political and cultural critiques embodied in the more mature writings of these two authors. Combining social and political thought, intellectual history, and literary interpretation, Goldman examines in particular Weber's "Science as a Vocation" and "Politics as a Vocation" and Mann's The Magic Mountain and Doctor Faustus.Goldman deals with the ways in which Weber and Mann sought an antidote to personal and cultural weakness through "practices" for generating strength, mastery, and power, drawing primarily on ascetic traditions at a time when the vitality of other German traditions was disappearing. Power and mastery concerned both Weber and Mann, especially as they tried to resolve problems of politics and culture in Germany. Although their resolutions of the problems they confronted seem inadequate, they show the significance of linking social and political thought to conceptions of self and active worldly practices.Trenchant and illuminating, Goldman's book is essential reading for anyone interested in political theory, social thought, and the intellectual history of Germany.
Frontmatter -- Contents -- Preface and Acknowledgments -- 1. Self and Power, Self and Nation -- 2. The Crises of Bildung and Science -- 3. Rationalization, Identity, and Death -- 4. The Identification of Self and Nation -- 5. Illness as a Vocation: The Magic Mountain -- 6. Ascetic Politics and the Empowered Self -- 7. The Nation, the Devil, and Power: Doctor Faustus -- Conclusion: Asceticism, Social Crisis, and the Overcoming of Redemption -- Notes -- Bibliography -- Index
Includes bibliographical references (pages 341-359) and index.
Print version record.
English.
JSTOR
Keywords: Weber, Max, -- 1864-1920 -- Contributions in political science; Mann, Thomas, -- 1875-1955 -- Political and social views; Mann, Thomas, -- 1875-1955; Weber, Max, -- 1864-1920; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; SOCIAL SCIENCE / Sociology / General; Political and social views; Political science; Cultuurkritiek; Zelf; Duitsland; Political Theory of the State; Political Science; Law, Politics & Government